2001
DOI: 10.1046/j.1471-4159.2001.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol exposure induces [Ca2+]i transients, cell swelling and transformation of actin cytoskeleton in astroglial primary cultures

Abstract: ] i transients in a small population of the cells. Cell swelling was estimated using a new method based on three-dimensional¯uorescence imaging in conjunction with image analysis and graphic visualization techniques. The method provides detailed results concerning the reformation of structural shape and speci®c volume alterations, as well as total proportions between the different states. Astroglial cell swelling was registered and quanti®ed in 7 of 39 cells chosen from 12 different coverslips. EtOH also induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 34 publications
7
59
1
Order By: Relevance
“…Others have seen morphological changes induced by LPS in cultured astrocytes (48,49). In line with earlier published data, the present findings confirm that there is a connection between rearrangement of actin filaments and changes in astrocytic morphology and cell volume (46,47).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Others have seen morphological changes induced by LPS in cultured astrocytes (48,49). In line with earlier published data, the present findings confirm that there is a connection between rearrangement of actin filaments and changes in astrocytic morphology and cell volume (46,47).…”
Section: Discussionsupporting
confidence: 93%
“…We found that the actin filaments were disorganized after many h of LPS exposure. The actin filaments, which are normally organized in stress fibers, changed into ring structures after 1 h of treatment and were disrupted and disorganized at 24 h. We have observed similar patterns previously when astrocytes were exposed to ethanol, ammonium chloride, or lactate (46,47). Others have seen morphological changes induced by LPS in cultured astrocytes (48,49).…”
Section: Discussionsupporting
confidence: 84%
“…We concluded this from results in nonpancreatic cells showing that ethanol influences PKC subcellular distribution and activity [21][22][23][24][25] and that it induces transformations of the actin cytoskeleton [26][27][28]. However, to our knowledge, pancreatic acinar cells have not yet been tested for such effects of ethanol.…”
Section: Introductionmentioning
confidence: 91%
“…Actin plays critical roles in shaping and maintaining cell morphology, as well as in supporting various cellular functions, including cell motility, cell division, and intra-cellular transport (Allansson et al, 2001). Physiological stress could lead to increasing number of actin-containing stress fibers and change the characteristic of the growth-arrested state of cells (Thomas et al, 1981).…”
Section: Effects Of As On the Proteome Of Juvenile Musselsmentioning
confidence: 99%